PENGARUH KORUPSI TERHADAP PEMBANGUNAN MANUSIA DI INDONESIA - Syahrul Hanafi (Wahana Islamika: Jurnal Studi Keislaman, 2018)
The success of development is not sufficiently measured by usingonly economic measures but also must be supported by noneconomic indicators. Where to measure the development of a State based on non-economic indicators that use Human DevelopmentIndex (HDI). But in its activities, developing countries in both Asiaand Africa are often hampered by high corruption practices. Basedon this the authors are interested to see the effect of corruption onthe provincial capitals in Indonesia. This study aims to see the effectof corruption in Indonesia as reflected in the Corruption PerceptionIndex (IPK) on human development (HDI). The research designused is quantitative analysis. Sampling is done by using judgmentsampling technique, where the research sample is some provincialcapital in Indonesia with the data fulfill the criteria, so total data is54 from 18 provincial capitals and three years of observation (2006,2008, 2010). The analytical technique used to answer all objectivesin this research is to use sregresi data panel analysis. The resultsshow that simultaneously corruption adversely affects humandevelopment. This means that the higher the level of corruption, thelower the human development, where the effect of corruption onhuman development of 11.06%.